Supramalleolar dome osteotomy after a childhood ankle fracture malunion: a case report - Alharkan, Talal S.; Alabbad, Raghad S.; Alhaddab, Yasser A.; Alhajjaj, Athkar H. (International Journal of Research in Orthopaedics, 2026)
Proper ankle alignment is essential for maintaining normal gait mechanics and balanced load transmission across the tibiotalar joint. Coronal plane malalignment, whether varus or valgus, alters joint loading patterns and increases stress on one side of the ankle, leading to progressive cartilage damage and the development of ankle osteoarthritis. If left uncorrected, such deformities may result in chronic pain, instability, functional decline, and reduced quality of life. We report the case of a 38-year-old woman with a residual varus ankle deformity secondary to childhood fracture malunion, who was successfully treated with dome supramalleolar osteotomy. This case highlights the role of the Dome shaped Supramalleolar osteotomy (SMO) as an effective joint-salvage procedure for distal tibial malalignment, demonstrating favorable clinical and patient-reported outcomes.